2007
DOI: 10.1016/j.jcrs.2006.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Profile of clear corneal cataract incisions demonstrated by ocular coherence tomography

Abstract: Results indicate an incision in the plane of the cornea with a chord length of at least 2.0 mm provides advantageous architecture for adequate self-sealing. Proper clear corneal incision construction resulted in an incision architecture that seemed to have increased stability and added safety, contributing to an absence of endophthalmitis for more than 10 years and 9000 cases in a single practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
86
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 6 publications
5
86
0
4
Order By: Relevance
“…This may be because a two-step clear corneal incision is arcuate in configuration (Figures 3a-e), rather than linear, and hence is more stable. 19 Lyles et al 20 similarly reported preservation of epithelial integrity on first post-operative day in their series. The presence of transient descemet membrane detachment and endothelial gape was elicited on first post-operative day in both groups.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This may be because a two-step clear corneal incision is arcuate in configuration (Figures 3a-e), rather than linear, and hence is more stable. 19 Lyles et al 20 similarly reported preservation of epithelial integrity on first post-operative day in their series. The presence of transient descemet membrane detachment and endothelial gape was elicited on first post-operative day in both groups.…”
Section: Discussionmentioning
confidence: 83%
“…Though ASOCT-assisted in vivo evaluation of wound architecture in patients undergoing phacoemulsification has been done previously, [19][20][21][22][23] we used ASOCT to compare manual vs the new motorized injector and to assess its safety, which has not been reported previously. No differences could be elicited between the two groups with respect to descemet's membrane detachment, anterior wound gape, and posterior gape at 1 month.…”
Section: Discussionmentioning
confidence: 99%
“…Изучена морфологическая картина [1][2][3] корнео-склерального тангенциального [4][5][6] и корнеального разрезов у больных с артифакией после факоэмуль-сификации катаракты. Для этого был использован оп-тический когерентный томограф RTVue-100 (Optovue, США).…”
Section: материалы и методы исследованияunclassified
“…Формирование роговичного разреза представляет собой один из основных этапов операции, важным свойством которого яв-ляется способность к плотному самостоятельному закрытию (самогерметизации) в конце операции, которая достигается за счет адгезии глубокого лоскута туннеля к поверхностному при сложной многопрофильной конфигурации разреза. Само-герметизация разреза играет важную роль в про-филактике послеоперационных инфекционных осложнений и быстрой реабилитации пациента [9,15,19].…”
unclassified
“…Такие разрезы выполняются под визуаль-ным контролем хирурга с помощью микроскопа, что не позволяет стандартизировать данный этап операции [5,19]. Разрез определяется следующи-ми характеристиками: доступ, локализация входа, ширина, длина, профиль и форма [5].…”
unclassified